Brechas de género en el mercado laboral y pobreza: Una aproximación a partir de microsimulaciones - Karen Marion Martínez Torrico (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2017)
– The achievement of gender equality in the labor market is not only a desirable goal by itself, but by its effects on growth and welfare. Based on such acknowledgement, this research quantifies the effects of gender gaps in employment, participation, occupational segregation and labor income, over monetary poverty in urban Bolivia. For this purpose, it is proposed to use the non-parametric microsimulation strategy in order to generate free gender gaps scenarios. Based on the comparison of poverty indicators observed and simulated with this strategy, it is evident that from 2006 to 2015 gender inequality in participation and labor income implied costs on the welfare of the society.
Keywords: C14; D31; I32; J7; J16; 330; Gender gaps; Poverty; Labor market; Microsimulation Techniques